2019
DOI: 10.1016/j.brainres.2018.02.045
|View full text |Cite
|
Sign up to set email alerts
|

Instructing neuronal identity during CNS development and astroglial-lineage reprogramming: Roles of NEUROG2 and ASCL1

Abstract: The adult mammalian brain contains an enormous variety of neuronal types, which are generally categorized in large groups, based on their neurochemical identity, hodological properties and molecular markers. This broad classification has allowed the correlation between individual neural progenitor populations and their neuronal progeny, thus contributing to probe the cellular and molecular mechanisms involved in neuronal identity determination during central nervous system (CNS) development. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 99 publications
(141 reference statements)
0
16
0
Order By: Relevance
“…Recent work in our laboratory has shown that the origin of astroglial cells, either from cerebral cortex or cerebellum, affects the phenotype of iNs lineage-converted by either ASCL1 or NEUROG2 (Chouchane et al, 2017 ). Notably, most iNs generated from astroglia from either cerebellum or neocortex showed central hallmarks of neurons commonly observed in those regions, suggesting that a “molecular memory” in the astroglial cells contributes to the acquisition of specific neuronal phenotypes in iNs (Chouchane and Costa, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in our laboratory has shown that the origin of astroglial cells, either from cerebral cortex or cerebellum, affects the phenotype of iNs lineage-converted by either ASCL1 or NEUROG2 (Chouchane et al, 2017 ). Notably, most iNs generated from astroglia from either cerebellum or neocortex showed central hallmarks of neurons commonly observed in those regions, suggesting that a “molecular memory” in the astroglial cells contributes to the acquisition of specific neuronal phenotypes in iNs (Chouchane and Costa, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…During CNS development, ASCL1 is expressed in progenitor cells committed to the generation of GABAergic interneurons [42,43]. For lineage reprogramming, ASCL1 converts astrocytes from different origins into neurons adopting mostly a GABAergic phenotype or a mix of glutamatergic and GABAergic phenotypes [29,43,44,45]. Therefore, immunocytochemical analysis was performed to examine the subtype of glioma cell-converted neurons using specific markers, including vGluT1 (excitatory interneuron marker), GABA (inhibitory interneuron marker) and ChAT (motor neuron marker).…”
Section: Resultsmentioning
confidence: 99%
“…Progenitors in the cerebellum and spinal cord express Neurog2 generate GABAergic and cholinergic neurons, respectively (Bertrand et al, 2002 ). Similarly, progenitors expressing Ascl1 contribute to different neuronal lineages in the cerebral cortex, cerebellum, and retina (Chouchane and Costa, 2018 ). Most protocols aiming at obtaining fibroblast-derived iNs with a particular phenotype through direct lineage reprogramming require the use of several TFs (Victor et al, 2014 ; Blanchard et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%